Blood flow dynamics with four-dimensional flow cardiovascular magnetic resonance in patients with aortic stenosis before and after transcatheter aortic valve replacement - Komoriyama, Hirokazu; Kamiya, Kiwamu; Nagai, Toshiyuki; Oyama-Manabe, Noriko; Tsuneta, Satonori; Kobayashi, Yuta; Kato, Yoshiya; Sarashina, Miwa; Omote, Kazunori; Konishi, Takao; Sato, Takuma; Tsujinaga, Shingo; et al. (Journal of cardiovascular magnetic resonance, 2021)
Pre- and post-procedural hemodynamic changes which could affect adverse outcomes in aortic stenosis (AS) patients who undergo transcatheter aortic valve replacement (TAVR) have not been well investigated. Four-dimensional (4D) flow cardiovascular magnetic resonance (CMR) enables accurate analysis of blood flow dynamics such as flow velocity, flow pattern, wall shear stress (WSS), and energy loss (EL). We sought to examine the changes in blood flow dynamics of patients with severe AS who underwent TAVR. We examined 32 consecutive severe AS patients who underwent TAVR between May 2018 and June 2019 (17 men, 82 ± 5 years, median left ventricular ejection fraction 61%, 6 self-expanding valve), after excluding those without CMR because of a contraindication or inadequate imaging from the analyses. We analyzed blood flow patterns, WSS and EL in the ascending aorta (AAo), and those changes before and after TAVR using 4D flow CMR. After TAVR, semi-quantified helical flow in the AAo was significantly decreased (1.4 ± 0.6 vs. 1.9 ± 0.8, P = 0.002), whereas vortical flow and eccentricity showed no significant changes. WSS along the ascending aortic circumference was significantly decreased in the left (P = 0.038) and left anterior (P = 0.033) wall at the basal level, right posterior (P = 0.011) and left (P = 0.010) wall at the middle level, and right (P = 0.012), left posterior (P = 0.019) and left anterior (P = 0.028) wall at the upper level. EL in the AAo was significantly decreased (15.6 [10.8-25.1 vs. 25.8 [18.6-36.2]] mW, P = 0.012). Furthermore, a significant negative correlation was observed between EL and effective orifice area index after TAVR (r = - 0.38, P = 0.034). In severe AS patients undergoing TAVR, 4D flow CMR demonstrates that TAVR improves blood flow dynamics, especially when a larger effective orifice area index is obtained.